Strategic development objectives of the western Balkan in the context of its faster integration into European Union - Izet Ibreljic; Salih Kulenovic (European Regional Science Association (ERSA), 2003)
Including the part of geospace of southeastern Europe in the region of western Balkan, EU experts had certain goal. This is as it is known specific part of european economical-political space of cca 265.000 km2 with close to 25 millions inhabitans where the politicians still do not have strategy which is determined or the vision of the future. It is one of the reason why for this part of the continent will take longer to be included in EU. First of all the goal of this paper is that, on the base of the available empiric data to perceive development limitations of western Balkan (low level of development, slow down transition, insufficient FDI, demographical problems etc) and then analyze in details priority goals of development in western-balkan (macroeconomical stability, liberalisation, the restructuring of economy, integration in the process of globalisation) and broad european (european benefit or costs due to faster or slower development of this part of eurospace) context. Of course, at the end it will be necessary to determine real possibilities of realisation these defined goals of development in the time that is coming.
Keywords: 330